Creating children Book Using ChatGPT - Weeldenburg, Nicolai; Depardieu, Agnieszka (International Journal of Art, Design, and Metaverse, 2023)
ChatGPT, short for “Chat Generative Pre-trained Transformer,” is an advanced artificial intelligence (AI) model that has revolutionized the field of conversational agents. This paper provides a comprehensive study on the capabilities, applications, and challenges of ChatGPT. The abstract delves into the technical intricacies of the model, exploring its underlying architecture and training process. Additionally, the abstract examines the practical applications of ChatGPT in various industries, from customer support to language translation and content generation. Furthermore, it discusses the ethical implications and potential risks associated with deploying AI-powered conversational agents. The abstract concludes by highlighting the transformative potential of ChatGPT and its role in shaping the future of AI-driven interactions.